Language learning strategy reported choice by bilingual children in CLIL: The effect of age, proficiency and gender in L3 learners of English. (December 2019) - Milla, Ruth; Gutierrez-Mangado, M. Juncal
Abstract: Research on language learning strategies (LLS) has widely investigated the relationship between adult second language (L2) learners' choice and use of LLS and different learner factors such as proficiency, age and gender. In the present study, these three variables are investigated in relation to the choice of LLS focusing on primary school bilingual learners in a CLIL context. Using a revised version of Oxford's (1990) survey, we collected data on the choice of LLS from Basque/Spanish bilingual learners of third language (L3) English in grades 5 and 6 primary education (age range 10–12; N = 131). Results show no differences in the amount and types of LLS chosen when proficiency and gender are considered separately. However, age seems to have a minimal effect in that grade 5 learners report using 'Remembering' more frequently than grade 6 ones. Additionally, proficiency seems to interact with gender in favour of males in that males in the lower beginner and beginner groups choose a wider range of LLS than females. However, this difference between males and females disappears in the upper beginner group. These findings are discussed in light of results from previous research of LLS choice by child L2 learners.